Adaptasi Perubahan Iklim Melalui Penerapan Drainase Berwawasan Lingkungan (Ecodrain) - Joleha Joleha; Bochari Bochari; Alifian Malik; Suprasman Suprasman; Elianora Elianora (Fakultas Teknik, 2023)
Climate change has an impact on increasing the temperature of the earth's surface which causes an increase in extreme weather such as floods and droughts. Climate change adaptation is an effort to increase the ability to adapt to changes, including climate diversity and extreme climate events, so that the potential damage caused by climate change can be reduced, opportunities posed by climate change can be utilized and the consequences can be overcome. This study discusses hydrological disasters due to climate change with a change adaptation approach, through environmentally sound drainage or ecodrain. One of the chosen forms of ecodrain is infiltration wells. Excess water that causes flooding can be reduced by storing excess water into the soil. Water that is absorbed into the soil is beneficial for the continuity of groundwater. From the results of the discussion, it is known that with extreme weather changes, evaporation exceeds the amount of rainfall in certain months in Pekanbaru City in 2018. The potential for water loss from this area results in the emergence of potential drought. However, as long as the annual rainfall value is greater than the evaporation value, the annual meteorological drought in the area can be avoided. On the other hand, the design of infiltration wells in the Hang Tuah Cipta Housing area is able to reduce runoff that occurs by 70% of the total runoff to be absorbed into the ground. Thus infiltration wells are able to provide benefits in reducing flooding and saving groundwater.